2020
DOI: 10.1111/1467-9566.13221
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacy and public health: preserving professionalism by extending the pharmacy gaze?

Abstract: Community pharmacy faces ongoing challenges to its economic and social standing. A concern to legitimate professional status explains the attraction of public health. Interventions currently advocated by UK State-sponsored health care seek to reconcile the autonomous 'entrepreneurial' patient with market-driven solutions. Engaging critically with recent Foucauldian sociological work on pharmacy as a conduit for disciplinary power, we explore how professional ambiguity is exploited to 'manage' the subjectivitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…This tension between meeting targets and the freedom to support clients resonates with the experiences of link workers in education (Fretwell, 2020) and of community pharmacists who were defined as much by policy as professional practice due to the ‘payments associated with contractual activity’ (Atkin et al., 2021, p. 339). Likewise, Sam described:
For me it’s incredibly frustrating to be based in practices where, if we were outside the [intervention] I would be busy from 6:00 am in the morning to 6:00 pm at night, very, very happily working with some people who need it…That imbalance is a result of structural strategic issues rather than patient need and is incredibly frustrating to me.
…”
Section: Resultsmentioning
confidence: 99%
“…This tension between meeting targets and the freedom to support clients resonates with the experiences of link workers in education (Fretwell, 2020) and of community pharmacists who were defined as much by policy as professional practice due to the ‘payments associated with contractual activity’ (Atkin et al., 2021, p. 339). Likewise, Sam described:
For me it’s incredibly frustrating to be based in practices where, if we were outside the [intervention] I would be busy from 6:00 am in the morning to 6:00 pm at night, very, very happily working with some people who need it…That imbalance is a result of structural strategic issues rather than patient need and is incredibly frustrating to me.
…”
Section: Resultsmentioning
confidence: 99%
“…We thus agreed Version 4 with the patient and pharmacy advisory groups, thus completing the planned intervention development process and proceeded with the pilot trial [ 49 ], which provided encouraging evidence of impacts, whilst identifying also the challenges involved in research participation for community pharmacists [ 50 ]. After we had completed the intervention development work we also examined in depth our experience of the nature of co-production with patients in the context of the relevant literature [ 51 ] and further analysed the nature of professionalism among pharmacists in respect of public health roles [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…CPs were more able to use certain person-centred consultation skills in routine practice to varying degrees. However, long standing professional habits and the busy, dispensing-focused, practice context incentivised reverting to more transactional and less person-centred practice (see ( Atkin et al., 2021 )). Scrutiny of, and feedback on, actual practice with patients have been identified as being likely key mechanisms for further empirical study in the RCT.…”
Section: Discussionmentioning
confidence: 99%
“…A scoping review of the MUR and NMS literatures found that few studies evaluated outcomes of MURs or the NMS ( Stewart, et al, 2019 ). To date only one RCT (of NMS) has been conducted ( Elliott et al., 2016 ), in addition to a few qualitative observational studies ( Atkin et al, 2021 ; Morris et al, 2019 ). Most research is retrospective and based on recall of what happens in consultations.…”
Section: Introductionmentioning
confidence: 99%